P362 Prospective study of phArmaCokinetics of InFliximab during induction in patients with Crohn's disease and ulcerative colitis (PACIFIC). (15th January 2020) - Liefferinckx, C; Bossuyt, P; Thomas, D; Rahier, J F; Louis, E; Baert, F; Dewint, P; Pouillon, L; Lambrecht, G; Vermeire, S; Franchimont, D
Abstract: Background: Loss of response (LOR) to infliximab (IFX) remains a challenge in routine management of IBD patients. We evaluated IFX high-resolution pharmacokinetics (PK) during induction with intermediate and peak PK levels. Methods: This is a prospective, multicentre ( n = 9), interventional study approved by EC (P2017/484). Fourteen blood samples were collected per patient from baseline to week 30. All patients were IFX naïve with active disease according to clinical, biological and endoscopy criteria. The primary outcome evaluated the inter-individual variability of IFX PK during induction and correlation with remission at week 30. In addition to trough levels (TLs), intermediate (ILs) and peak levels (PLs) were also measured and defined as drug level between two infusions and drug level early on after infusion (+2h), respectively. Remission was defined as having a Harvey Bradshaw Index (HBI) ≤ 4 and C-Reactive Protein (CRP) ≤5 for Crohn's disease (CD), and as a clinical Mayo score ≤2 and faecal calprotectin <250 µg/g for ulcerative colitis (UC). IFX samples were measured by ELISA (Apdia) while a drug-tolerant affinity capture elution anti-infliximab assay was used to measure anti-infliximab antibodies (ATI) at weeks 6, 22 and 30. Results: Demographic and baseline data of the study population are presented in Table 1. Among the 62 patients enrolled, 33.9% of patients ( n = 21/62) were in remission at week 30. Eight patients dropped out due to disease worsening. Median TLs at week 6 were higher among patients in clinical remission at week 30 ( p = 0.02) confirming previous observations. However, ILs at day 3 as well as PLs after the third infusion were also significantly higher in patients in clinical remission at week 30 (Figure 1a–c). ATI were detected as soon as week 6. At week 2, infliximab levels were significantly lower among patients in which ATI developed at a later time point ( p = 0.006) and this observation was confirmed when measuring ILs at day 17 ( p = 0.002), TLs at week 6 ( p = 0.002) and ILs at week 10 ( p = 0.001). Conclusion: This multicentre prospective study demonstrates that intermediate levels as early as day 3 predict remission at week 30 in IBD patients. Low IFX levels during induction were correlated to future ATI development. PK modelling may allow to better select patients early on for sustained remission with infliximab.